Impact of the COVID-19 pandemic on social media marketing (COVID-19–ის პანდემიის გავლენა სოციალურ მედია მარკეტინგზე) - Todua (თოდუა), Nia (ნია) (Ivane Javakhishvili Tbilisi State University Press, 2022)
The article illustrates the role of social media in business. Particular attention is paid to the growth of social media marketing activities in the context of the COVID-19 pandemic. The study identified the main reasons why consumer activity increased on social media due to the COVID-19 pandemic. The paper shows respondents' assessments of how social media supports solving the problems caused by the COVID-19 pandemic. The article also defines which area should be most active on social media regarding the COVID-19 pandemic
1. Al-Sheikh, E. S., & Hasanat, M. H. A. (2020). Social media mining for assessing brand popularity. In Global Branding: Breakthroughs in Research and Practice (pp. 803-824). IGI Global. 2. Apil, A. R., Kaynak, E., and Todua, N. (2009). Product Preference Differences of High and Low Ethnocentric Consumers in Georgia. In Proceedings of the 18th World Business Congress „Management Challenges in an Environment of Increasing Regional and Global Concerns“,International Management Development Association, pp. 531-539. 3. Coursaris, C. K., van Osch, W., & Balogh, B. A. (2016). Do Facebook likes lead to shares or sales? Exploring the empirical links between social media content, brand equity, purchase intention, and engagement. In 49th Hawaii international conference on system sciences (HICSS) (pp. 3546-3555). IEEE. 4. DataReportal (2021). Digital 2021: Georgia. Produced by Simon Kemp and the team at Kepios. Available at https://datareportal.com/reports/digital-2021-georgia (Accessed January 27, 2022). 5. Eurostat (2022). Social media - statistics on the use by enterprises. Available at: https://ec.europa.eu/eurostat/statisticsexplained/index.php?title=Social_media_-_statistics_on_the_use_by_enterprises (Accessed January 27, 2022). 6. Hajli, N., Sims, J., Zadeh, A. H., & Richard, M. O. (2017). A social commerce investigation of the role of trust in a social networking site on purchase intentions. Journal of Business Research, 71, 133-141. 7. Jashi, Ch. (2020). The New Context of Marketing in Social Media (Conceptual review). Economics and Bussines, 1, 152- 164. 8. Kaplan, A. M., & Haenlein, M. (2010). Users of the world, unite! The challenges and opportunities of Social Media. Business horizons, 53(1), 59-68. 9. Malhotra, N. (2010). Marketing research: An applied orientation. 6th ed., Upper Saddle River, N.J.; London: Pearson Education. 10. Mghebrishvili, B., & Urotadze, E. (2021). Challenges of Business Social Responsibility in the Conditions of Coronavirus Pandemic. Ecoforum Journal, 10(3). 11. Saunders, M., Lewis, P., & Thornhill, A. (2019). Research methods for business students. 8th ed., Harlow: Pearson Education Ltd. 12. Seturi, M., & Urotadze, E. (2020). Some opinions about sustainable development and tourism (case of Georgia). In Proceedings of the 5th International Scientific and Practical Conference „Strategic imperatives of modern management“ (Kyiv National Economic University named after Vadym Hetman), pp. 286-289. 13. Statista (2021a). Global digital population as of January 2021 (in billions). Available at: https://www.statista.com/statistics/617136/digital-population-worldwide/ (Accessed January 27, 2022). 14. Statista (2021b). Social media usage in the United States - Statistics & Facts. Available at: https://www.statista.- com/topics/3196/social-media-usage-in-the-united-states/ (Accessed January 27, 2022). 15. Statista (2021c). Social media usage in Europe - Statistics & Facts. Available at: https://www.statista.com/- topics/4106/social-media-usage-in-europe/ (Accessed January 27, 2022). 16. Todua, N. (2019). Using social media marketing for attracting foreign tourists to Georgian destinations. Globalization and Business, 7, 39-48. 17. Todua, N., & Jashi, C. (2018). Influence of Social Marketing on the Behavior of Georgian Consumers Regarding Healthy Nutrition. Bulletin of the Georgian National Academy of Sciences, 12 (2), 183-190. 18. Todua, N., Mghebrishvili, B., & Urotadze, E. (2016). Main aspects of formation of legal environment on the Georgian food market. In Proceedings of the International Scientific Conference „Challenges of Globalization in Economics and Business“Ivane Javakhishvili Tbilisi State University, pp. 250-256. 19. Urotadze, E. (2020). The role of social media marketing in attitude towards Georgian consumers to travel agencies. In Proceedings of the 7th Business Systems Laboratory International Symposium „Socio-Economic Ecosystems: Challenges for Sustainable Development in the Digital Era“, University of Alicante (Spain), pp. 236-241. 20. Usman, A., & Okafor, S. (2019). Social Media and Purchase Intentions: Strategic Marketing Implications. In W. Ozuem, E. Patten & Y. Azemi (Eds.), Harnessing Omni-Channel Marketing Strategies for Fashion and Luxury Brands (pp. 83-105). Irvine: BrownWalker Press. 21. Xhema, J. (2019). Effect of Social Networks on Consumer Behaviour: Complex Buying. IFAC-PapersOnLine, 52(25), 504- 508.
Keywords: COVID-19 pandemic, social media, marketing, consumer behavior, marketing research